GINGIVAL SMILE CORRECTION USING THE FLAPLESS TECHNIQUE: A CASE REPORT - Da Sois Vaccari , Luana; Tomasi , Lorenza; Pereira Butze, Juliane (Health and Society, 2023)
Introduction: The gummy smile is characterized by the extensive display of gingiva when smiling and ends up unfavoring the aesthetic aspect, generating dissatisfaction in many patients. This gingival disharmony has several etiologies and, taking into account that each individual presents their uniqueness, it is essential that the dentist knows the cause of each clinical situation, so that an effective, specific and respective treatment plan can be elaborated to the patient’s complaint. Objective: The present work aimed to present, through a case report, a gummy smile treatment using the “Flapless” technique. Case report: A 20-year-old female patient sought care in the undergraduate course in dentistry at the Centro Universitário da Serra Gaúcha – FSG, complaining of a gummy smile. The proposed treatment plan was a gingival surgery, using the “Flapless” technique, associated with the application of botulinum toxin, which would intensify the result of the gummy smile correction. However, after the surgical healing, the patient approved the result of the procedure and chose to end the treatment. Conclusion: Based on the clinical case presented, it was possible to conclude that gingival surgery through de Flapless technique was effective for the correction of the gingival smile, the patient obtained the desire result, without the need to associate other techniques to achieve the aesthetics of the smile.